A closer look at neophyte teachers' instructional competence: A phenomenological study - Lynard Bobby L. Asirit; Jocelyn H. Hua; Lorenzo Mendoza (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The concept of instructional competence, which refers to the ability to show that one has the readiness and effectiveness of necessary skills within the teaching framework in public schools, has hardly ever been investigated. This qualitative descriptive phenomenological study aimed to discover the instructional competence of newly hired public school teachers. Through the lens of Albert Bandura's (1997) Self-Efficacy Theory, it investigated what instructional competencies a newly hired teacher possessed that demonstrated readiness and efficacy of the required skills. The focus group discussions highlighted the crucial characteristics for improving the competencies. The results revealed six (6) emergent themes: the acquisition of baseline instructional standards, coping with the shift of instructional quality, planning for quality instruction, an initiative for instructional improvement, dealing with uncertainties, and health and well-being stability. The results highlighted that instructional competency might become self-efficient with increased experience and practice. Their prior teaching experience influenced the quality of a new teacher's instruction. In addition, teachers' competencies are gradually enhanced and strengthened as they gain experience in the field. As students discover new concepts, teachers begin to hone the skills that will allow them to manage classroom instruction effectively. This study deepens the understanding of instructional competence and may enable teachers and policymakers to design and implement initiatives. Since there is strong evidence that newly hired teachers may be self-sufficient, instructional managers must assure support by creating policies and programs that bridge instructional competencies to practice. These professional development programs allow newly hired teachers eventually gain instructional competency and well-motivated public-school teaching.